Pengembangan dan Validasi Instrumen Keterampilan Berpikir Kritis Siswa SMA pada Materi Dinamika Rotasi: Pendekatan Rasch Model - Abdul Salam; Lina Aviyanti; Nur Endah Susilowati; Silmi Fitriani; Rahma Malizka (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Critical thinking is a core competency required in 21st-century education, but a valid and reliable instrument for assessing this skill within the topic of rotational dynamics remains limited. This study aims to develop and validate a critical thinking skills assessment instrument for senior high school students on the topic of rotational dynamics, employing the Rasch model for comprehensive validation. Instrument development followed the ADDIE model, involving 34 students during the implementation and evaluation phases. The instrument comprises 27 items constructed based on Facione's critical thinking aspects. Content validity analysis yielded a mean Aiken's V of 0.93, exceeding the critical threshold of 0.80. Unidimensionality testing revealed a raw variance explained by measures of 28.9% (>20%), with unexplained variance in contrasts 1–5 of the PCA residuals ranging from 5.8% to 9.9% (<15%), indicating that the instrument consistently measures a single construct. Twenty-six of the 27 items demonstrated fit to the Rasch model. Reliability analysis yielded an item reliability of 0.81 (good), a person reliability of 0.68 (fair), and a Cronbach's Alpha of 0.72 (good). Wright Map and Item Characteristic Curve (ICC) analyses further confirmed the alignment between item difficulty levels and student ability levels. The developed instrument is demonstrated to be valid and reliable for measuring critical thinking skills among senior high school students in the context of rotational dynamics.